Quality of Life in Vulvar Lichen Sclerosus Patients Treated With Long-Term Topical Corticosteroids. Issue 2 (April 2021) - Wijaya, Marlene; Lee, Geoffrey; Fischer, Gayle; Lee, Andrew
Abstract : Objective: The aim of the study was to investigate the quality of life in vulvar lichen sclerosus (VLS) patients treated with long-term, individualized topical corticosteroids. Methods: A prospective cross-sectional study comparing new pretreatment and long-term treated VLS patients attending a dermatogynecology practice in Sydney, Australia. Participants were invited to complete the Vulvar Quality of Life Index (VQLI). The VQLI scores were compared between the 2 groups. Results: A total of 204 biopsy-proven VLS patients—68 new pretreatment and 136 treated patients on topical corticosteroids for 2 years or longer. Treated participants scored lower in all VQLI components, including total score (median = 2.0 [interquartile range IQR = 0.0–6.0] vs 13.5 [IQR = 7.5–22.0]; p < .001), symptoms (median = 0.5 [IQR = 0.0–0.5] vs 1.3 [IQR = 0.8–2.0]; p < .001), anxiety (median = 0.0 [IQR = 0.0–0.3] vs 0.8 [IQR = 1.1–2.0]; p < .001), activities of daily living (median = 0.2 [IQR = 0.0–0.3] vs 0.5 [IQR = 0.2–1.1]; p < .001), and sexuality (median = 0.0 [IQR = 0.0–0.7] vs 1.0 [IQR = 0.0–2.0]; p < .001). A higher proportion of treated patients achieved total scores of 0–5, representing nil to minimal impact of VLS on quality of life (98 [72.1%] vs 8 [11.8%]; p < .001). Mild and reversible adverse effects were developed in 11 patients (8.1%). Partially compliant patients were 12 times as likely to develop scarring progression than fully compliant patients (7 [22.6%] vs 2 [1.9%]; p < .001). Conclusions: Long-term, individualized topical corticosteroid treatment is safe and effective in maintaining disease remission and improves the quality of life of VLS patients. Fully compliant patients demonstrate better treatment outcomes than partially compliant patients. Abstract : Supplemental digital content is available in the text.